Deforestation and economics in Ecuador: a synthesis - Wunder, Sven (Royal Veterinary and Agricultural University, 2001)
This synthesis paper gives an economic perspective on the analysis of deforestation. Ecuador provides a versatile picture of factors affecting forest loss throughout different periods, regions and ecosystems. The main fieldwork was carried out over 18 months in 1994-5 and focused on semi-structured socio-economic interviews in nine sites in the Ecuadorian highlands, as well as on the urban markets for forest and agricultural products that the study sites are linked to. The study areas differ in terms of biophysical conditions and production models. But, surprisingly the basic dynamics of deforestation were much alike across the sample, with the same driving forces and motives for rural change. In contrast to the situation in the highlands, deforestation on the coast has been much more influenced by leading export crops, such as cocoa and bananas. Examples of the forest-clearing incentives for bananas are provided: changing world-market demand and altering banana production technologies and derived settlement patterns greatly influenced land demand and forest conversion in the coastal region. It is shown that macroeconomic changes and domestic policy responses greatly influenced the historical speed of forest clearing. Summing up, the standard arguments of policy and market failures alone can not explain rapid deforestation in Ecuador. A root cause is that, with current technologies, prices and disparate stakeholder interests, natural forest uses in Ecuador tend to yield less income than alternative, mainly agro-pastoral land uses. The deforestation cycle usually follows a composite economic rationale, based on wood extraction, agriculture and cattle ranching. Though a slower pace of deforestation seems rational for the Ecuadorian State, on the basis of precautionary considerations, substantial success in curbing forest loss can only be achieved when payments for global forest benefits are combined with effective conservation incentives on the ground. Finally, lessons from the Ecuador case to deforestation processes in general are outlined, and a number of priority areas for future research are identified.